Uji Aktivitas Antioksidan Minyak Buah Merah (Pandanus Conoideus Lam.) Secara In Vitro dan In Vivo pada Tikus Yang Diberi Beban Aktivitas Fisik Maksimal - Sandhiutami, Ni Made Dwi; Ngatidjan, Ngatidjan; Kristin, Erna (Jurnal Sains dan Teknologi Farmasi, 2010)
Increasing oxygen consumption during intensive physical exercise may increase production of free radicals, and if it exceeds physiological capacity may cause oxidative stress as shown as chance of MDA level. Buah merah oil contains high betacarotene and tocopherol, as well as fatty acid such as oleic acid, linoleic acid, linolenic acid and decanoic acid. Tocopherol is major biological lipid-soluble antioxidant, protecting structures and function of cell membranes from free radicals. The objective of this study was to know in vitro antioxidant activity and the effect of buah merah oil on MDA level in blood during maximum physical activity treatment. In vitro antioxidant activity test was conducted using DPPH method (2,2-diphenyl-1-picryl hydrazyl). In vivo antioxidant activity test was done by using 24 male Wistar rats in pre - post test control group design. The rats were grouped into 4 groups. The control group was given destillated water and three treatment groups were given buah merah oil in the dose of 0,15 ml/kgBW; 0,3 ml/kgBW; 0,6 ml/kgBW respectivelyfor 10 days. Before buah merah oil was given, level of MDA was measured. Ten days later, the four group were given maximum physical activity mean of swimming until the sign of fatigue occurred (nearly drowned) and the blood was taken for blood MDA examination. In vitro, the IC50 of buah merah oil was 451,51 Î¼g/ml. In vivo test, dosage 0,15 ml/kgBW could decrease MDA 5,22% Dosage 0,3 ml/kgBW could decrease MDA 11,96% and dosage 0,6 ml/kgBW could decrease MDA 8,19% . Buah merah oil showed antioxidant activity in vitro. In vivo experiment, all dosage of buah merah oil decreased blood MDA level but in the dose of 0,3 ml/kgBW decreased MDA level more than dose of 0,15 ml/kgBW and 0,6 ml/kgBW.